Production Of Ethanol By Genetically Modified Saccharomyces Cerevisiae Using Sago Starch As Substrate - Ang, Dek Chang (2001)
The performance of direct fermentation of sago starch to ethanol by three strains of genetically modified Saccharomyces cerevisiae, YKU 107 (expressing a.-amylase), YKU 131 (expressing glucoamylase) and YKU 132 (expressing a.-amylase and glucoamylase), was investigated. In fermentation using 2 L fermenter, we found that strains YKU 107, YKU 131 and YKU 132 was capable to hydrolyse 83.45%,67.45% and 71.9% of sago starch, respectively. However, only strain YKU 131 has the ability to produce significant amount of ethanol (2.16 gL-1) from sago starch. The superiority of strain YKU 131 as compared to strain YKU 107 and YKU 132 was found to be correlated with its ability to secrete glucoamylase. S. cerevisiae YKU 131 was selected for further studies. To investigate the performance of S. cerevlszae YKU 131 in ethanol production using various types of starch, initial starch concentration was fixed at 20 gL-1 Among different types of starch investigated, com starch was the most susceptible to the glucoamylase, followed by sago, cassava, potato and rice starch.